If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 14 = -2x + 26 Reorder the terms: 14 + x = -2x + 26 Reorder the terms: 14 + x = 26 + -2x Solving 14 + x = 26 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 14 + x + 2x = 26 + -2x + 2x Combine like terms: x + 2x = 3x 14 + 3x = 26 + -2x + 2x Combine like terms: -2x + 2x = 0 14 + 3x = 26 + 0 14 + 3x = 26 Add '-14' to each side of the equation. 14 + -14 + 3x = 26 + -14 Combine like terms: 14 + -14 = 0 0 + 3x = 26 + -14 3x = 26 + -14 Combine like terms: 26 + -14 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| x^3-11x^2-20x=0 | | 5x+1=3x+8 | | x+-4=-8 | | -7x-16=-3x-12 | | 5x-11=-2x+31 | | 8x+13=11x-23 | | 24t-.8t^2=90 | | 6x-15=12x+20 | | 5r+3r=10 | | x^3+4x-2=0 | | 24t-8t^2=90 | | 9x+3x-10=3(3x+1) | | 8x^2+29x+15= | | 2/10= | | 4x^2-12x+45=0 | | 12x-17=6x+25 | | x^3+2x^2=520 | | Isy=2x-3 | | (x^2)-2x+1=0 | | 18+-(18)= | | -2x-3=-7 | | ln(x-2)+ln(x+2)=ln(2x+11) | | 4x^2-23x+39=2x+3factorize | | 27j-6=17j+7 | | 4x-2=9x-3 | | 2y+12=4y-4 | | 12+10=5a+7-8a | | 4t-6=6t+12 | | x^3+2x^2-520=0 | | 4x+7=8x-7 | | ln(x)=3-ln(2x) | | 53+34= |